Удачные последствия неудачного сватовства: Н. И. Тургенев в Англии (1829—1830) [Successful Consequences of a Failed Suit: Nikolai Turgenev in England (1829—1830)] - Vera Mil’china (Slavica Revalensia)
The article of Prof. Vera Mil’china (RSUH / ИВГИ РГГУ, RANEPA / ШАГИ РАНХиГС) is based on Nikolai Turgenev’s unpublished correspondence, and explores an unknown episode from a Decembrist’s life story: his attempt to marry a daughter of a British squire. Turgenev’s letters show that this plan was one of the reasons why he reconsidered returning to Russia, where he had received in absentia a death penalty (later changed to a life-long hard labor term). In the beginning of 1830, Turgenev made the decision to return to Russia to affect a retrial that would allow him to overturn his conviction for high treason. However, none of this came to fruition: Turgenev did not marry Harriet Lovell and did not return to Russia.